HOST RANGE PANTOEA ANANATIS THE CAUSAL AGENT OF BACTERIAL LEAF BLIGHT ON ALLIUM SPP. - Asrul Asrul; Umrah Umrah (Universitas Tadulako, 2019)
Bacterial leaf blight disease caused by Pantoea ananatis has been reported affects some species of Allium spp. Here, we determined the species of Allium spp. that are not the hosts of the P.ananatis through a host range test. The study designed as a completely randomized design with five replications. Pathogenic bacteria of P. ananatis inoculated to shallot, onion, spring onion, garlic, chives, leek, and cung spring onion in the greenhouse of the Faculty of Agriculture Tadulako University. The incubation period and symptoms of after inoculated by P. ananatis then observed. The results showed that four llium species (onion, onion, scallion, and garlic) were hosts of P. ananatis while the other three species (chives, leek, and cung spring onion) were not hosts of P. ananatis.